Fur Seals : Maternal Strategies on Land and at Sea - Kooyman, Gerald L.; Gentry, Roger L. (Book collections on Project MUSE., 1986)
The contributors to this volume have accomplished a breakthrough in our ability to collect data on ocean-dwelling mammals. In the first large-scale comparison of fur seals, they have employed quantitative methods and a special instrument called a Time-Depth-Recorder to study the strategies used by females in six species of cared seals to rear and wean their young in different environments. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.